UMA LEITURA HELENÍSTICA DO PENSAMENTO ARISTOTÉLICO: OIKEIÔSIS E JUSTIÇA EM ANTÍOCO DE ASCALÃO - da Rosa, Cláudia Beltrão (PHOÎNIX, 2020)
This paper, focuses the fate, in Hellenistic period, of Aristotle's moral and political philosophy, one which in its original version clearly does make the polis, and its kind of relationships, important in ethical thought. We possess a passage of great interest, in which we find attempts to recast and update Aristotle's theory in ways which are heavily influenced by Stoicism: the Antiochus' theory as put forwards in Book V of Cicero's De Finibus.